The Association of Left Ventricular Hypertrophy with Sudden Cardiac Death in Hypertension: A Systematic Review - Adzana Yasadhy Hangga Prasetyo (International Medical Journal Corp. Ltd, 2025)
Introduction: Left ventricular hypertrophy (LVH), a common manifestation of hypertension-mediated organ damage, is a potent predictor of adverse cardiovascular outcomes. However, a comprehensive synthesis of its specific association with sudden cardiac death (SCD) in hypertensive populations is needed. This systematic review aims to identify, appraise, and synthesize the evidence quantifying the link between LVH and SCD in hypertension, exploring the prognostic value of various anatomic and electrical markers of hypertrophy. Methods: Following PRISMA guidelines, a systematic search of PubMed, Scopus, Embase, and the Cochrane Library was conducted to identify prospective cohort studies and clinical trials reporting on the association between LVH and SCD in hypertensive adults. Studies were screened for eligibility, and data on study design, population, LVH assessment, and risk estimates were extracted. The methodological quality of included studies was assessed using the ROBINS-I tool for non-randomized studies. Results: Seventeen cohort studies and post-hoc analyses of clinical trials, encompassing over 50,000 patients, were included. The evidence consistently demonstrates that LVH is a powerful and independent predictor of SCD. Echocardiographically defined LVH was associated with a more than two-fold increase in SCD risk (Hazard Ratio 2.16; 95% Confidence Interval [CI] 1.22–3.81), while electrocardiographically (ECG) defined LVH conferred a nearly three-fold increased risk (adjusted HR 2.99; 95% CI 1.47–6.09). Specific LVH phenotypes, including concentric geometry, the presence of an ECG strain pattern (adjusted HR for cardiovascular mortality 1.53; 95% CI 1.18–2.00), prolonged QRS duration (HR per 10 ms increase 1.22; p<0.001), and QTc interval prolongation (Odds Ratio 1.72; 95% CI 1.23–2.40), were identified as markers of particularly high risk. Furthermore, therapeutic regression of LVH was associated with a significant reduction in SCD risk, with the absence of in-treatment LVH lowering the risk by up to 30% (HR 0.70; 95% CI 0.54–0.92). Discussion: The association between LVH and SCD is underpinned by a triad of arrhythmogenic mechanisms: structural remodeling (myocardial fibrosis), electrophysiological instability (altered ion channel function and repolarization abnormalities), and relative myocardial ischemia. These pathophysiological changes create a vulnerable substrate for fatal ventricular arrhythmias. The findings highlight that ECG and echocardiography provide complementary, rather than redundant, prognostic information, reflecting distinct electrical and anatomic aspects of myocardial remodeling. Conclusion: LVH is a clinically significant and modifiable risk factor for SCD in patients with hypertension. Risk stratification in hypertension should extend beyond blood pressure measurement to include a comprehensive assessment of LVH. The presence of high-risk features, such as concentric geometry or an ECG strain pattern, warrants more aggressive management aimed at LVH regression to mitigate the risk of sudden death.